The calming campus: using green infrastructure on college campuses to help reduce stress - Tilley, Joel (My University, 2025)
College campuses are the primary locations where students spend most of their time during their college careers and a place that some even call home. This relationship between students and their campus demands that the campus support the needs of the students. However, this is often not the case, as many college green spaces do not support student activity but operate as special event spaces. This lack of student-focused green space design relates to the mental health crises many campuses are facing. Importantly, research has concluded that the simple act of viewing and interacting with a natural environment can help manage feelings of depression, reduce feelings of stress, and improve one’s self-esteem. While therapeutic gardens are not a substitute for therapy, they help maximize the healing potential of green space through designs that lessen users’ feelings of stress and anxiety. To fully maximize the healing potential of therapeutic gardens, design professionals have taken an interest in artistic green infrastructure to provide these mental health benefits in a way that appeals to campus developers through the additional benefit of stormwater management. This research area has recently gained attention as a response to climate change, and deeper evaluations of therapy gardens and green infrastructure systems are needed to help intertwine green infrastructure systems into therapeutic gardens and promote the well-being of students on college campuses.
Keywords: Green infrastructure; Artful rainwater design; Artistic green infrastructure; Well-being; Campus design; Eco-revelatory design